(3eYGfj GdCNHGQs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CHhGH GdcJGH GdHGH GdChd GdPj ef CLdg SejfG gPG GdcJGH (B... (3MOKfG eMeO Hf GdMSf Hf CMeO Hf GdhdjO (B... (3bGd SeYJ CHG YHO Gddg Ydjg GdSdGe jbhd(B: (3CfJe Cabg GdfGS(B...s
(3BNQgG (B:s
(3ceG bGd Gddg YR hLd(B: (3dJONdf GdeSLO GdMQGe Ef TGA Gddg Befjf(B. (3hgh jYde Cfge jONdhfg ChdG hbO Sei Gddg GdeDefjf HGdYed GdUGdM (B... (3Je GdcJGH hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B274s
(3GdPQjYI HQbe(B: 4622s
(3GdPQjYI HQbe(B: 4622s
(3GdCYdGe(B: (3L(B6(3, U(B274s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs